Validation of the standardised assessment of personality – abbreviated scale in a general population sample. (27th August 2015) - Fok, Marcella Lei‐Yee; Seegobin, Seth; Frissa, Souci; Hatch, Stephani L.; Hotopf, Matthew; Hayes, Richard D.; Moran, Paul
Abstract Background Personality disorder (PD) is associated with important health outcomes in the general population. However, the length of diagnostic interviews poses a significant barrier to obtaining large scale, population‐based data on PD. A brief screen for the identification of people at high risk of PD in the general population could be extremely valuable for both clinicians and researchers. Aim We set out to validate the Standardised Assessment of Personality – Abbreviated Scale (SAPAS), in a general population sample, using the Structured Clinical Interviews for DSM‐IV Personality Disorders (SCID‐II) as a gold standard. Method One hundred and ten randomly selected, community‐dwelling adults were administered the SAPAS screening interview. The SCID‐II was subsequently administered by a clinical interviewer blind to the initial SAPAS score. Receiver operating characteristic analysis was used to assess the discriminatory performance of the SAPAS, relative to the SCID‐II. Results Area under the curve for the SAPAS was 0.70 (95% CI = 0.60 to 0.80; p < 0.001), indicating moderate overall discriminatory accuracy. A cut point score of 4 on the SAPAS correctly classified 58% of participants. At this cut point, the sensitivity and specificity were 0.69 and 0.53 respectively. Conclusion The SAPAS operates less efficiently as a screen in general population samples and is probably most usefully applied in clinical populations. © 2015 The Authors Personality and Mental Health published by John Wiley & Sons Ltd